Spatial distribution and multilevel analysis of determinants of measles in Malaysia, 2018-2022 - Daud, Mohd Rujhan Hadfi Mat (2024)
Background: Measles remains a significant public health challenge worldwide, including in Malaysia, despite high vaccination rates and comprehensive control strategies. The persistent fluctuations in measles incidence across districts highlight the complexity of controlling this disease, which is influenced by a multitude of demographic, environmental, and healthcare-related factors. This study aims to analyse the spatial distribution of measles, explore the determinants of its transmission, and understand the impact of individual and contextual factors on its incidence in Malaysia from 2018 to 2022. Methods: This study integrates three distinct analytical approaches using data sourced from the Disease Control Division of the Ministry of Health Malaysia, the e-measles database, and additional demographic and environmental data from the Department of Statistics Malaysia and the Department of Environment Malaysia. Spatial autocorrelation techniques, including Global Moran’s I and Local Indicators of Spatial Association (LISA), were used to identify measles hotspots and clustering effects. A negative-binomial mixed-effect model was employed to assess the impact of healthcare access, demographics profile, and environmental factors on measles incidence. Furthermore, multilevel logistic regression analysis examined the relationship between measles infection and both individual-level factors such as age, gender, ethnicity, travel history, nationality status, contact history, travel history and vaccination status and district-level determinants including population density, median household income, urbanisation, number of healthcare facility, vaccination coverage, PM2.5, relative humidity and temperature. Results: The analysis identified significant districts like Bintulu, Marudi, Miri, and Gua Musang with measles incidence rates exceeding 500 per million population in specific years. A general decline in incidence from 2018 to 2021, followed by a slight increase in 2022, was observed. Spatial autocorrelation analysis confirmed the presence of clustering of measles cases in Malaysia with persistent hotspots in certain regions, particularly in Klang Valley. Significant factors influencing measles incidence included median household income (aIRR 1.02, 95% CI: 1.01, 1.03), number of healthcare facilities (aIRR 1.02, 95% CI: 1.01, 1.04) and temperature (aIRR 0.85, 95% CI: 0.74, 0.99). The odds of getting measles are higher among older age (aOR 1.02, 95% CI 1.02,1.03), indigenous ethnic (aOR 6.80, 95% CI 4.88,9.48), non-Malaysian (aOR 34.53, 95% CI 8.42,141.51), those with contact history (aOR 2.36, 95% CI 2.07,2.69) and those with travel history (aOR 2.30, 95% CI 1.13,4.70). An increase in one dose of measles vaccine in an individual reduces the risk of measles infection by 24% (aOR 0.76, 95% CI 0.72,0.79). For contextual factors, urbanisation was significantly associated with measles infection (aOR 1.56, 95% CI 1.16,2.10) and the more health and rural clinics in a district an individual resides in, the lower the risk of measles infection (aOR 0.98, 95% CI 0.97,0.99) adjusted for the clustering effect of the district. Conclusions: There is presence of continuous threat of measles transmission in Malaysia that may hinders the achievement of the elimination target. Thus, effective management of the disease require a comprehensive approach that combines detailed epidemiological surveillance, socio-economic interventions, and personalised healthcare strategies.